2022
DOI: 10.1097/acm.0000000000004911
|View full text |Cite
|
Sign up to set email alerts
|

Research Methodologies in Health Professions Education Publications: Breadth and Rigor

Abstract: Purpose Research methodologies represent assumptions about knowledge and ways of knowing. Diverse research methodologies and methodological standards for rigor are essential in shaping the collective set of knowledge in health professions education (HPE). Given this relationship between methodologies and knowledge, it is important to understand the breadth of research methodologies and their rigor in HPE research publications. However, there are limited studies examining these questions. This study synthesized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…While this chapter focuses on illustrating how epistemology is foundational to teaching and learning, it would be incomplete without recognizing that epistemic beliefs also lay the foundation for HPE scholarship. Most HPE research and scholarship is grounded in post‐positivism, resulting in calls for studies with alternate epistemological underpinnings (Han et al., 2022; Regehr, 2010). As several have asserted, HPE could be strengthened through valuing and employing epistemological diversity, which might be best achieved by interdisciplinary collaborations (Hayes & Doherty, 2017; Varpio & MacLeod, 2020).…”
Section: Hpe Scholarshipmentioning
confidence: 99%
See 1 more Smart Citation
“…While this chapter focuses on illustrating how epistemology is foundational to teaching and learning, it would be incomplete without recognizing that epistemic beliefs also lay the foundation for HPE scholarship. Most HPE research and scholarship is grounded in post‐positivism, resulting in calls for studies with alternate epistemological underpinnings (Han et al., 2022; Regehr, 2010). As several have asserted, HPE could be strengthened through valuing and employing epistemological diversity, which might be best achieved by interdisciplinary collaborations (Hayes & Doherty, 2017; Varpio & MacLeod, 2020).…”
Section: Hpe Scholarshipmentioning
confidence: 99%
“…Researchers have recently begun to call for HPE journal editors to create opportunities for research with different epistemic underpinnings. This could include pursuing articles that reflect a broader array of epistemologies (Han et al., 2022), diversifying editorial boards (Yip & Rashid, 2021), and recruiting reviewers with more diverse perspectives (Krlev & Spicer, 2023).…”
Section: Hpe Scholarshipmentioning
confidence: 99%
“…A third example, referenced earlier, is Van Nistelrooij and Visse’s (2019) exploration of the dynamics of professional responsibility to provide care in a nursing environment. In the HPE context, phenomenological research contributes to innovation by filling “methodological gaps” identified in a large-scale analysis of methods employed in HPE research (Han et al, 2022, para 1).…”
Section: Heidegger and Hermeneutic Phenomenologymentioning
confidence: 99%
“…Han et al 8 conducted a descriptive quantitative study to examine current trends in methodologies and rigor in health professions education (HPE). Their work found that HPE primarily used quantitative methodologies, and that there was a lack of "subjectivist epistemologies and philosophical frameworks highlighting critical inquiry, feminism, and postmodernism. "…”
Section: Critical Approaches To the Literaturementioning
confidence: 99%
“…Han et al 8 conducted a descriptive quantitative study to examine current trends in methodologies and rigor in health professions education (HPE). Their work found that HPE primarily used quantitative methodologies, and that there was a lack of “subjectivist epistemologies and philosophical frameworks highlighting critical inquiry, feminism, and postmodernism.” This is an important paper because it raises larger questions about how knowledge is created in our profession, what methodologies are leading these efforts, and the potential consequences in staying with the current trends.…”
Section: Critical Approaches To the Literaturementioning
confidence: 99%